Food Design and Social Innovation: didactic experience report (Revista de Ensino em Artes, Moda e Design, 2024)
With the expansion of design possibilities, areas such as social innovation and food design have emerged. While there are existing papers that connect design, sustainability, social innovation, and food, few delve into issues related to design education. To address this gap, this article utilizes an experience report as a means of constructing scientific knowledge. It describes and analyzes the teaching experience of the elective course "Food Design and Social Innovation," offered to third-year undergraduate design students. This curricular unit employed active teaching and learning methodologies, including the flipped classroom and project-based learning. A bibliographic review supported the planning of the course and its critical reflective analysis, which was also informed by student evaluations. Overall, the assessment of the course was positive, despite some identified limitations and suggestions for improvement. The use of active methodologies proved beneficial for engagement and learning, with the opportunity to explore new design possibilities addressing socio-environmental issues highlighted as a key differentiator.
Keywords: design for social innovation; design teaching; food design; active methodologies